Challenges and Solutions in Hydropower: Analyzing Francis Turbine Performance and Operational Dynamics - Mochamad Denny Surindra; Baktiyar Mei Hermawan; Suwarti; Slamet Priyoatmojo; F. Gatot Sumarno (Eksergi, 2025)
This paper addresses the global challenge of sustainable energy, exploring alternatives to dwindling fossil fuels and rising CO2. While renewables like solar and wind offer potential, they face geographical and intermittent limitations. Thermal and nuclear energies are discouraged due to severe environmental and health impacts. Hydropower emerges as a highly reliable and favored global solution, harnessing energy from flowing water, tides, and dams. It's the most prevalent renewable source for electricity, offering consistent, dependable, and emission-free supply. The Francis turbine is crucial to hydropower, known for its high efficiency. Its spiral casing, runner, and guide vanes efficiently convert water's energy into electricity. Water flows from a reservoir to the turbine, where guide vanes regulate entry to the runner, driving a generator. Our analysis reveals key factors affecting hydropower performance: energy source, guide vane opening, servomotor performance, and governor control system. Sediment accumulation at the inlet causes head loss, reducing optimal output. Misaligned guide vane openings can drop rotational speed, leading to suboptimal load. Servomotor issues like wear also require maintenance. A 5% speed drop setting effectively manages water pressure and flow, enabling smooth load escalation.